Mr. Deeds - Brill, Steven, 1950-; Covert, Allen, 1964-; Erick Avari; Jared Harris; John Turturro; Peter Gallagher; Winona Ryder; Adam Sandler (USA Columbia Pictures Corporation, 2002)
When Longfellow Deeds, a small-town pizzeria owner and poet, inherits
A sweet-natured, small-town guy inherits a controlling stake in a media conglomerate and begins to do business his way.
Clarence Budington Kelland
Languages: English, Russian, Hungarian Subtitles: English, Spanish, Arabic, Bulgarian, Czech, Danish, Finnish, Greek, Hebrew, Hindi, Hungarian, Serbo-Croatian, Icelandic, Norwegian, Polish, Russian, Slovenian, Swedish, Turkish, Romanian
Keywords: Romance; Comedy